Pengaruh Lingkungan Kerja dan Beban Kerja terhadap Kinerja Karyawan pada PT. Pegadaian Cabang Palopo - Nur Afni; Muhammad Kasran; Sukri Sukri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the effect of work environment and workload on employee performance at PT. Pegadaian Palopo Branch. The research method used is a quantitative approach with a saturated sampling technique, so that the entire population of 40 employees was used as respondents. Data were obtained through online questionnaires and analyzed using SPSS version 19. The results showed that the work environment had a positive and significant effect on employee performance, while workload had no significant effect. These findings emphasize that a conducive work environment can enhance employee productivity and achievement, while workload is not always a determining factor of performance. Therefore, the company is advised to focus more on improving the quality of the work environment as the main strategy in enhancing employee performance.